Pengaruh Kualitas Layanan Dan Nilai Yang Dirasakan Peserta Terhadap Kepuasan Peserta Dengan Kepercayaan Sebagai Variabel Mediasi Pada Pt Taspen (Persero) Kantor Cabang Yogyakarta - M. Thomi Sirojudin; Henny Welsa; Nonik Kusuma Ningrum (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to examine and analyze the influence of service quality and perceived value of participants on participant satisfaction with trust as a mediating variable. This research was conducted at the company PT Savings Fund and Civil Servant Insurance or PT. TASPEN (Persero) Yogyakarta Branch Office. Data collection was carried out using a questionnaire that was given in person and online to recipients of civil servant pensions who had entered retirement from 2021 to 2022. The number of research samples was 120 samples. The analysis tool used was multiple linear regression with the help of SPSS 16 software. The results showed that the service quality variable had a positive and significant effect on trust, the value felt by participants had a positive and significant effect on trust, service quality had a positive and significant effect on participant satisfaction, score perceived by participants has a positive and significant effect on participant satisfaction, participant trust has a positive and significant effect on participant satisfaction. Furthermore, participants' trust was not able to mediate the effect of service quality on participant satisfaction, but participants' trust was able to mediate the effect of participants' perceived values ​​on participant satisfaction